Quality assessment of peanut butter produced in Miagao, Iloilo - Marcella, Catherine May B. (2004.)
The study was conducted to assess the quality of raw peanuts and local peanut butter (Miagao, Iloilo).
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Quality assessment; Peanut butter; Miagao, Iloilo